1970
DOI: 10.5713/ajas.2013.13137
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Municipal Abattoir Conditions and Animal-related Factors on Avoidance-related Behaviour, Bleeding Times at Slaughter and the Quality of Lamb Meat

Abstract: The objective of this study was to determine the effect of municipal abattoir conditions and animal factors on avoidance-related behaviour (AB) of sheep at slaughter, bleeding times (BT) and mutton quality. The behaviour of 66 castrates and 19 ewes of different age categories was observed at three stages of slaughter. Higher behaviour scores indicated higher levels of AB. Time intervals between the start of blood flow and the time the flow changed from a constant stream into drips were recorded as BT. Thirty t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 29 publications
0
10
1
Order By: Relevance
“…Multiple indicators such as response behaviour towards certain stimuli and the biochemical changes (in the blood, urine, excreta) have been used to quantify animal welfare in different conditions Gruber et al, 2010;Njisane & Muchenje, 2013a;Njisane & Muchenje, 2013b). In addition, avoidance-related behaviour and vocalization have been used to determine animal welfare in abattoirs (Grandin 1998;Manteuffel et al, 2004;Hemsworth et al, 2011;Njisane & Muchenje, 2013a;Njisane & Muchenje, 2013b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple indicators such as response behaviour towards certain stimuli and the biochemical changes (in the blood, urine, excreta) have been used to quantify animal welfare in different conditions Gruber et al, 2010;Njisane & Muchenje, 2013a;Njisane & Muchenje, 2013b). In addition, avoidance-related behaviour and vocalization have been used to determine animal welfare in abattoirs (Grandin 1998;Manteuffel et al, 2004;Hemsworth et al, 2011;Njisane & Muchenje, 2013a;Njisane & Muchenje, 2013b).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, avoidance-related behaviour and vocalization have been used to determine animal welfare in abattoirs (Grandin 1998;Manteuffel et al, 2004;Hemsworth et al, 2011;Njisane & Muchenje, 2013a;Njisane & Muchenje, 2013b). However, it should be noted that animals of the same species but varying genetically may exhibit differing response-behaviour patterns (Grignard et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…These behavioural observations have been used only in a general way without quantification such as signs of distress (jumping, bellowing, trembling, moving backwards and frequent urination). It has been reported that animals waiting for slaughter could be stressed by handling and novelty of the pre-slaughter environment (that is, the abattoir set-up), adverse weather conditions, hunger, thirst and fatigue (Muchenje et al, 2009a;Bourguet et al, 2011;Njisane & Muchenje, 20013a). A combination of behavioural and physiological measures has been used to assess animal welfare (Broom, 2000;Ndou et al, 2011).…”
Section: Non-invasive Assessment Of Methods Of Stressmentioning
confidence: 99%
“…This could be a reflection of the situation in many developing countries. Most slaughterhouses in rural African communities do not measure up to appropriate standards, suggesting a need to train and monitor these abattoir personnel and properly fur nish the facilities for efficient and safe operation [47,55,74,75].…”
Section: Animal Welfare In African Conditionsmentioning
confidence: 99%